The Function of the Demonic in Illness and Dying - Ungar-Sargon, Julian (Archives of Clinical and Biomedical Research, 2026)
This essay traces the development of the demonic (or daemonic) as an interpretive category for the experience of illness and dying. Surveying texts from the Hebrew Bible, Greek philosophy, early rabbinic literature, medieval Kabbalah, Christian demonology, and modern depth psychology (especially C.G. Jung), the essay argues that the “demonic” is not merely a supernatural force but an existential structure of experience—a symbolic form through which humans interpret suffering, powerlessness, and the limits of agency. Across these traditions, illness becomes a site where human mastery collapses and where the daemonic, representing both dread and hidden meaning, breaks into consciousness. The demonic threatens destruction, yet paradoxically becomes the source of integration, insight, and spiritual transformation: the triumph of the daemon over mere egoic will. An addendum extends this analysis to addiction, exploring how substance use disorders manifest the daemonic structure with particular intensity—the experience of possession by alien compulsion, the collapse of will, and the paradoxical path to recovery through surrender and spiritual transformation.